Bonding of silicon nitride ceramic by ultrafast high temperature sintering - Gan, Ming Zhen (Nanyang Technological University, 2023)
Silicon nitride, Si3N4 is one of the advanced ceramics that is widely used in engineering industries due to its attractive properties such as high temperature stability and hardness. Due to the difficulty in fabricating complex shaped and large size components, the application of Si3N4 has been restricted. Joining of Si3N4 parts is required to widen its application. In this study, ultrafast high sintering (UHS) will be used to carry out the joining process. UHS has been proven to sinter ceramics in a short amount of time, but little study has been done on using UHS to join ceramics. Comparing UHS and conventional sintering method, UHS is a much faster process. In conventional sintering, thermal degradation of the substrate may happen, which might contaminate the samples.